1983
DOI: 10.1126/science.221.4606.117
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication as a Scientific Tool

Abstract: Research in microfabrication not only serves the microelectronics industry but also can provide research tools for studying the behavior of matter at submicrometer dimensions. A variety of techniques including optical, x-ray, and electron beam lithography and reactive ion etching can be used to make structures, devices, and arrays only hundreds of atoms across. Microfabrication techniques have been applied to experiments on surface-enhanced Raman scattering, transport in one-dimensional conductors, and macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 47 publications
0
18
0
2
Order By: Relevance
“…17 A series of subsequent experiments confirmed that noble metal films with roughened surfaces or nanoscale patterns can dramatically increase Raman scattering signals of analytes and produce enhancement factors (EFs) of 10 4 –10 8 over normal Raman scattering. 21, 22 …”
Section: Introductionmentioning
confidence: 99%
“…17 A series of subsequent experiments confirmed that noble metal films with roughened surfaces or nanoscale patterns can dramatically increase Raman scattering signals of analytes and produce enhancement factors (EFs) of 10 4 –10 8 over normal Raman scattering. 21, 22 …”
Section: Introductionmentioning
confidence: 99%
“…The urge to miniaturize electronic circuitry and memory devices originates from demands such as reduced cost of ingredient materials, compactness, low weight and high reliability, and low power requirements, among others 1. As the size of the active device components as well as of the metallic interconnects is projected to decrease well below 100 nm, one of the pertinent questions being addressed is how to cast materials at such small length scales and derive acceptable device characteristics 2. It has been a dream of researchers to learn to cast materials at the nanoscale with the ease and versatility of everyday writing, stamping, or molding where the desired “material ink” is directly deposited.…”
mentioning
confidence: 99%
“…The use of this method requires the fabrication of a photomask (PM) and the deposition of a photoresist (PR) (Fig. 15.1a), which involve several technological steps: PM conception/realization and PR deposition, baking, insulating, and developing [8]. Typically, nanofluidic channels are made by using a conventional lithography step followed by dry or wet etching to define the depth of the channel [9].…”
Section: Tools For Nanosystems Prototypingmentioning
confidence: 99%